Enhancing intercultural communication skills in foreign language teaching - Kushchenko, Zhanna L. (Національний технічний університет "Харківський політехнічний інститут", 2024)
This comprehensive article explores the multifaceted process of developing intercultural communication skills in foreign language teaching. It deals with the significance of these skills, strategies for their enhancement, and the impact on learners. The article aims to provide educators with an in-depth understanding of fostering intercultural competence in language education.

У статті досліджується багатогранний процес розвитку навичок міжкультурної комунікації під час викладання іноземної мови. У ній йдеться про важливість цих навичок, стратегії їхнього розвитку та вплив на студентів. Стаття має на меті надати освітянам поглиблене розуміння розвитку міжкультурної компетентності у мовній освіті.
Keywords: intercultural communication; foreign language teaching; cultural competence; language education; cross-cultural communication; intercultural awareness